Mapping Students' Problem-Solving Skills in Physics Subject After Inquiry Learning at Class X SMAN 1 Prambanan - Putri, R Z; Jumadi, J; Ariswan, A; Kuswanto, H (Department of Physics, Faculty of Mathematics and Natural Sciences, 2019)
Problem-solving skills is necessary to be mastered by students to help them in solving the problems of their daily life in the future. The purpose of this study was to map the student problem-solving skills after inquiry learning in Physics subject, impulse, and momentum in class X SMAN 1 Prambanan, Yogyakarta. Experimental research model with one-shot case study design was used in this study. Data collection was performed through essays at the end of the learning process. The results of the mapping show that students have different problem-solving skills levels at each stage. At the stage of problem identification, students were in a very good category. At the stage of planning the problem solution and problem-solving implementation, the students were in a good category, while in results evaluation, the students were in a fairly good category. The result of this study can contribute to giving the point of view to the teacher about students' problem-solving skills level based on the indicators as well as giving the additional information as a literature in the topic of students’ problem-solving skills after inquiry learning.